(untitled) (Международный научный журнал «Инженер», 2026)
In this paper, the importance of psychological and pedagogical disciplines — psychology, pedagogy, social psychology, developmental psychology, and pedagogical acmeology — is substantively examined as a fundamental and system-forming basis for students’ professional development and the formation of their project-based thinking in higher education. It is shown that these disciplines are not an optional addition to the curriculum, but constitute its internal core, giving the educational process meaningfulness and a human-centered dimension.